Whole cell three phase bioreactors allow for effective production of fatty acid alkyl esters derived from microalgae lipids. (15th March 2015) - Araya, K.; Ugarte, A.; Azócar, L.; Valerio, O.; Wick, L.Y.; Ciudad, G.
Highlights: Feasible whole cell catalysis process to produce FAAE from microalgae lipids. The efficiency of the process is related to the complexity of carbon source used (lipids). The hyphae have an important role in mass transfer since they may acts as pipeline. Temperature affected the quantity of alcohol added, not the fungi activity. Abstract: Lipids of the microalgae Botryococcus braunii and Nannochloropsis gaditana were used in a novel whole cell three-phase bioreactor (WCTB) using Rhizopus oryzae as biocatalyst for biodiesel (fatty acid alkyl esters, FAAE) production. The effects varying running conditions (the microalgae lipid, type of acyl acceptor, temperature, nutrient availability, alcohol to lipid ratio, and agar surface area exposed to gas-phase alcohol of varying convective fluxes) on the FAAE yield were studied and optimal conditions for the reactor identified. We found that the complexity of carbon source used (lipids) was related to the efficiency of the process, since it is used for both, growth and FAAE production, hence N. gaditana lipids were a more suitable raw material for FAAE production compared to B. braunii lipids due their higher content of fatty acid. The optimal operational conditions for our work were 20 °C and 8:1 alcohol to lipid volumetric ratio, where the best results was obtained using N. gaditana lipids as raw material and ethanol as acyl acceptor, reaching a FAAE yield of 92%. The results of our work indicate that both mass transfer process and the availability of nutrients are the most important variables in the performance of WCTB, where the hyphae have an important role in mass transfer since they may acts as 'pipeline', connecting different phases with the different components of the three phase bioreactor. These results should be considered as key design factors for developing the three phase bioreactor configuration.